1995
DOI: 10.1038/nsb1295-1102
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional structure of human lysosomal aspartylglucosaminidase

Abstract: The high resolution crystal structure of human lysosomal aspartylglucosaminidase (AGA) has been determined. This lysosomal enzyme is synthesized as a single polypeptide precursor, which is immediately post-translationally cleaved into alpha- and beta-subunits. Two alpha- and beta-chains are found to pack together forming the final heterotetrameric structure. The catalytically essential residue, the N-terminal threonine of the beta-chain is situated in the deep pocket of the funnel-shaped active site. On the ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
191
4

Year Published

1996
1996
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 172 publications
(199 citation statements)
references
References 32 publications
4
191
4
Order By: Relevance
“…The GGT heterodimer has a stacked ␣␤␤␣-core; the ␤-strands of the L and S subunits form the two central ␤-sheets, which are sandwiched by ␣-helices. The topology of GGT is similar to those observed for Ntn-hydrolase superfamily members such as aspartylglucosaminidase (22) and penicillin acylase (23). The ␤-strands comprising the two central ␤-sheets and nearby ␣-helices are topologically conserved among the members of this superfamily; the main-chain atoms of the 66 residues comprising the core of E. coli GGT are superimposable on those of human aspartylglucosaminidase with a rms deviation of 1.3 Å.…”
Section: Resultsmentioning
confidence: 59%
“…The GGT heterodimer has a stacked ␣␤␤␣-core; the ␤-strands of the L and S subunits form the two central ␤-sheets, which are sandwiched by ␣-helices. The topology of GGT is similar to those observed for Ntn-hydrolase superfamily members such as aspartylglucosaminidase (22) and penicillin acylase (23). The ␤-strands comprising the two central ␤-sheets and nearby ␣-helices are topologically conserved among the members of this superfamily; the main-chain atoms of the 66 residues comprising the core of E. coli GGT are superimposable on those of human aspartylglucosaminidase with a rms deviation of 1.3 Å.…”
Section: Resultsmentioning
confidence: 59%
“…The funnel is formed by loops that connect the two P-sheets and by loops connecting the smaller P-sheet and a-helices associated with it. Oinonen et al (1995) published the structure of human glycosylasparaginase in free form and as a complex with aspartic acid. All residues that bind aspartic acid in the human enzyme are contributed by two loops, P-strand B2 to p-strand B3, and P-strand B4 to a-helix B 1.…”
Section: Resultsmentioning
confidence: 99%
“…This is primarily caused by the changes in the conformations of the loops between a-helix A2 and p-strand A2 and between P-strand B6 and p-strand B7, which are among the loops that differ most between the two enzymes, and by differences in some residues at the edge of the cleft, most notably the substitution of Gln 254 in the bacterial enzyme for Phe 278 in the human enzyme. The latter substitution is significant because Oinonen et al (1995) suggested that Trp 11 and Phe 278 may be important for oligosaccharide binding. Although Trp 11 is conserved, the substitution of Gln for Phe 278 does not preclude this observation because both aromatic and polar-neutral residues are equally suitable for oligosaccharide binding, although with possible differences in specificities.…”
Section: Resultsmentioning
confidence: 99%
“…Bacterial L-asparaginases were the first threonine amidohydrolases described in the literature. Only recently, two other threonine amidohydrolases, 20S proteasome [14] and aspartylglucosaminidase [15], have been reported. Both enzymes belong to the nonrelated superfamily of N-terminal nucleophile (Ntn) hydrolases [16].…”
mentioning
confidence: 99%